Research Perspectives on Plasmodium knowlesi Malaria - Amirah Amir; Fei Wen Cheong; Meng Yee Lai; Wen-Chyau Lee; Jeremy Ryan de Silva; Jonathan Wee Kent Liew; Yee Ling Lau (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter explores the different aspects of research in malaria including risk factors, diagnosis, treatment, molecular and functional studies, mainly focusing on publications from the last five years. Plasmodium knowlesi is a zoonotic malaria parasite that has gained increasing medical interest over the past two decades. This zoonotic parasitic infection is prevalent in Southeast Asia and causes many cases with fulminant pathology. In almost all of Southeast Asia’s countries, as well as among visitors returning from these nations, human instances of human knowlesi have been recorded since the 2004 revelation of a significant concentration of cases in Sarawak. There are several factors leading to the increase of reported P. knowlesi cases. These include better diagnostic capacity, decreasing human malaria cases which in turn reduces relative immunity, increased awareness to P. knowlesi and close proximity of humans with natural reservoir hosts or infected vectors due to changes in human land use. Microscopy is the gold standard for malaria diagnosis but has its limitations as ring forms of P. knowlesi resemble P. falciparum and trophozoites and schizonts resemble those of P. malariae, and hence cannot be reliably differentiated. In-depth population genetic studies for both human and primate isolates are needed to shed light on possible human-to-human transmission of P. knowlesi and more importantly for us to understand the disease epidemiology and to guide knowlesi infection control.